Kualifikasi Tindak Pidana Love Scam dan Kekosongan Norma dalam Perspektif KUHP 2023 di Indonesia - Dewi Indah Safira; Rahadi Wasi Bintoro; Zaid Abdul Azis (Bulletin of Community Engagement, 2026)
The rapid development of information and communication technologies has transformed patterns of social interaction through digital spaces and facilitated the emergence of various forms of technology-based crime. One of the fastest-growing forms is love scam or online romance fraud, a type of deception conducted through digital platforms by establishing emotional intimacy with victims to obtain financial benefits. Unlike conventional fraud, love scams combine emotional manipulation, digital identity fabrication, and the exploitation of online communication platforms (Whitty & Buchanan, 2012; Wang & Topalli, 2022). Despite its increasing prevalence, the legal classification of love scams under Indonesian criminal law remains unclear, particularly when examined within the framework of Law Number 1 of 2023 on the Criminal Code (KUHP 2023) and the Electronic Information and Transactions Law (ITE Law). This study aims to analyze the legal qualification of love scams under KUHP 2023 and the ITE Law, as well as to identify existing normative gaps through a comparative legal approach. The research employs a normative legal methodology using statutory, conceptual, and comparative approaches. The findings indicate that love scams constitute a form of cyber-enabled fraud situated at the intersection of conventional fraud and cybercrime. KUHP 2023 does not explicitly accommodate the digital dimension and emotional manipulation inherent in such offenses, while the ITE Law does not specifically regulate fraud committed through personal and romantic relationships. This regulatory gap creates legal disharmony and normative uncertainty. Therefore, criminal law reform is necessary through either an expanded interpretation of fraud offenses or the establishment of specific legal provisions addressing love scams, in order to ensure legal certainty and provide comprehensive protection for victims.